Additional CCAFS Target Regions: Recommendations to the ISP - Thornton, Philip K.; Förch, Wiebke (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
In 2012, CCAFS plans to add two additional target regions to its portfolio, in order to make the program truly global. This document outlines the process for the selection of the two new regions, presents some analysis, and provides recommendations to the ISP.